Bioelectrical impedance analysis of high blood pressure patients / S.J. Lahvanya Raoov Subramaniam - S.J. Lahvanya Raoov, Subramaniam (2012)
Bioimpedance is a specialized field under constant development. In biomedical engineering, bioimpedance is a term used to describe the response of a living organism to an externally applied electric current. Other than that, bioelectric impedance analysis is one of the famous analyses many clinical applications. It is also considered as a new technique relatively for analyzing body composition. In most of the cases, the reliability and the accuracy that the analyzer carries made it suitable in estimating body composition in human. In this study, about 70 patients were used in which 35 of them are healthy (without high blood pressure or other diseases) and the remaining 35 are high blood pressure patients. Bioelectrical impedance analyzer was used to analyze bioimpedance parameters and biocomposition parameters such as body mass index (BMI), total body water (TBW), intracellular water (ICW), extracellular water (ECW), fat free mass (FFM) and basal metabolic rate (BMR). Comparison was done between the normal subject and the patients. For the most accurate results, the subjects are made sure that they did not eat for 4 hours prior to testing. They also should not have done any exercise for 12 hours prior testing, did not consume alcohol for 24 hours prior testing, did not drink caffeine on the day of the test, and did not wear pantyhose during the test. Positive result of the study will exhibit standard range of value of body composition among high blood pressure patients.